Digital Dashboards for Summative Assessment and Indicators Misinterpretation: A Case Study - Cisel, Matthieu (Canadian Journal of Education/Revue canadienne de l’éducation, 2022)
Over the last decade, teachers in France have been increasingly pressured to use digital learning environments, and to shift from grade-based to skill-based assessment. Educational dashboards, which measure student input electronically, could foster such a transition by providing insights into learners’ performances. However, such dashboards could also foster data misinterpretation during the summative assessment process, should the indicators that they display be used without a proper understanding of what they reflect. This article presents a methodology to detect potential mistakes in the interpretation of the indicators in the context of inquiry-based learning. During the design of a learning environment, we analyzed, through analytics and classroom observations in primary and middle schools, the issues that could arise from the use of a dashboard. Our data suggest that the amount of information practitioners needed to collect to make indicators relevant was burdensome, making the dashboard unfit for assessment purposes at the scale of a classroom.